Aeromedical retrieval to a university hospital emergency department in Scotland. Issue 1 (20th December 2004) - Caldow, S J; Parke, T R J; Graham, C A; Munro, P T
Abstract : Rural and island areas of Scotland benefit from the availability of the Scottish Ambulance Service paramedic staffed helicopter for transfers and primary scene responses. There are a small number of patients who require advanced airway management, invasive procedures, or critical care interventions to stabilise them before transport to definitive care. At present these additional skills are provided on an ad hoc basis by senior medical staff drawn from intensive care and emergency medicine at the receiving hospitals. Given the potential difficulties of training paramedics to use these infrequently used skills it may be preferable to establish a formalised system to access suitably trained medical staff. This case series illustrates the clinical challenges and potential benefits of such a service and discusses the practicalities involved.